In vitro antidiabetic potential of hydroethanolic leaf extract of sesbania sesban (L) - ARULSATHIYA K; RAGAVAN B (International Journal of Pharma and Bio Sciences, 2019)
Diabetes mellitus is a heterogeneous metabolic disorder characterized by hyperglycemia. This hyperglycemic elevation is associated with hyperlipidemia and alteration in carbohydrate and protein metabolism. The present study was carried out to evaluate the invitro antidiabetic activity of 50% ethanolic leaf extract of Sesbaniasesban (L) (family: Fabaceae). Upon the antidiabetic properties the inhibition of the α-amylase, α-glucosidase, glucose diffusion and amylolysis kinetics were examined. It was a dose-dependent increase in percentage inhibitory activity against α-amylase & α-glucosidase enzyme. Moreover, the adsorption capacity of the extract was directly proportional to the molar concentration of the glucose. Thus there is an urge for the therapeutic approach to decrease the postprandial hyperglycemia. The rate of glucose diffusion across the membranes was found to increase from 30-180 mins. In vitro assays suggests that the extract poses good antidiabetic potential. This knowledge will be useful in finding more potent antidiabetic principle from the natural resource for the clinical application.